Do American Youth Football Players Intentionally Use Their Heads for High-Magnitude Impacts?. Issue 14 (December 2019) - Alois, Jaclyn; Bellamkonda, Srinidhi; Campolettano, Eamon T.; Gellner, Ryan A.; Genemaras, Amaris; Beckwith, Jonathan G.; Greenwald, Richard M.; Smith, Eric; Rowson, Steven; Duma, Stefan M.; Crisco, Joseph J.
Background: Concern for head injuries is widespread and has been reported by the media to be the number one cause of decreased participation in football among the American youth population. Identifying player mechanisms associated with intentional, or purposeful, head impacts should provide critical data for rule modifications, educational programs, and equipment design. Purpose: To investigate the frequency of intentional and unintentional head impacts and to examine the player mechanisms associated with intentional high-magnitude head impacts by comparing the impact mechanism distributions among session type, player position, and ball possession. Study Design: Cross-sectional study; Level of evidence, 3. Methods: Head impact sensors and video footage of 68 players were used to analyze and classify 1319 high-magnitude impacts recorded over 1 season of youth football. Results: In total, 80% of the high-magnitude head impacts were classified as being caused by intentional use of the head. Head-to-head impact was the primary impact mechanism (n = 868; 82.7%) within the 1050 intentional high-magnitude impacts, with classifiable mechanisms, followed by head-to-body (n = 139; 13.2%), head-to-ground (n = 34; 3.2%), and head-to-equipment (n = 9; 0.9%). Head-to-head impacts also accounted for a greater proportion of impacts during practices (n = 625; 88.9%) than games, for linemen (n = 585; 90.3%) than perimeters and backs, and for ball carriers (n = 72; 79.1%) than tacklers. Conclusion: Overall, the majority of high-magnitude head impacts were intentional and resulted from head-to-head contact. The proportion of head-to-head contact was significantly higher for practices than games, linemen than backs and perimeter players, and ball carriers than tacklers.